The communicative education of fine arts in the COVID-19 crisis and its manifestations in the modernization of the works of the Iraqi painter "Nabil Ali as a model" (Al-Academy, 2021)
This study attempts to address the importance of communicative digitization in the field of various arts for the sake of continuity of shopping and aesthetic, artistic and intellectual appreciation of artistic achievements by the recipient on various places of their residence in light of the COVID 19 crisis, and to highlight the importance of the plastic arts of the Iraqi painter exclusively and how it expresses in a contemporary way the environment or life reality in Iraq in light of this crisis. With all its implications affecting the life reality from various aspects and methods of its negative and positive employment. As for the research procedures, the researcher reviewed the research methodology represented by the descriptive analytical approach and the research sample, which included (4) samples, and concluded by analyzing samples, as the most important results were reviewed, among which were: The COVID-19 had an impact on the production and creativity of the contemporary Iraqi artist that accumulated from the life reality (negative and positive to combat it) in the human community in light of this crisis, and that digital communication appeared in COVID-19 in a large way and its importance for the continuation of artistic cultural communication for artistic achievements